The Arab Awakening : America and the Transformation of the Middle East - Pollack, Kenneth M. (Kenneth Michael), 1966- (Book collections on Project MUSE., 2011)
Even the most seasoned Middle East observers were taken aback by the events of early 2011. Protests born of oppression and socioeconomic frustration erupted throughout the streets; public unrest provoked violent police backlash; long-established dictatorships fell. How did this all happen? What might the future look like, and what are the likely ramifications for the United States and the rest of the world? In "The Arab Awakening", experts from the Brookings Institution tackle such questions to make sense of this tumultuous region that remains at the heart of U.S. national interests. The first portion of "The Arab Awakening" offers broad lessons by analyzing key aspects of the Mideast turmoil, such as public opinion trends within the "Arab Street"; the role of social media and technology; socioeconomic and demographic conditions; the influence of Islamists; and, the impact of the new political order on the Arab-Israeli peace process. The next section looks at the countries themselves, finding commonalties and grouping them according to the political evolutions that have (or have not) occurred in each country. The section offers insight into the current situation, and possible trajectory of each group of countries, followed by individual nation studies. "The Arab Awakening" brings the full resources of Brookings to bear on making sense of what may turn out to be the most significant geopolitical movement of this generation. -- Publisher description.